The TESTS OF pH, CONDUCTIVITY, TOTAL DISSOLVED SOLIDS, SALINITY AND TURBIDITY IN THE BATANG ARAU RIVER SURROUNDING, PADANG CITY-WEST SUMATRA - Rusli HAR; Aprisal; Isril Berd; Lambok M. Hutasoit; Denny Akbar Tanjung (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
Humans need fresh water for many functions, including cleaning, irrigating plants, drinking, cooking, industrial uses, and more. It cannot be denied that the excessive exploitation of the environment by humans is the cause of the current decline in water quality. This study aims to test water quality such as pH, conductivity, total dissolved solids, salinity, and turbidity. The research method uses quantitative methods. The research area was taken from 10 subdistricts around the Arau River Basin. The sample is measured using a predetermined measuring instrument. Based on the test results from all research areas, several parameters for testing water quality meet the standards of the 2010 Ministry of Health Regulations, such as the pH test except for the Indarung and Lubuk Begalung sub-districts. and East Padang. The Total Dissolved Solids test in all areas is in good water standard except for Koto Tangah. The salinity test for all areas met the requirements for water quality standards except for the West Padang sub-district and the Turbidity test showed that all areas had turbidity values > 5 NTUs..